Between narrative and rhetoric in movie trailers - Dornaletetxe, Jon (Ámbitos. Revista Internacional de Comunicación, 2019)
The aim of this paper is to better understand the relationship between narrative thinking and rhetoric in movie trailers. For that purpose, an experiment on trailer comprehension and preference was conducted with 239 students. On one hand, variables concerning narrative comprehension of the story the trailers show were measured and, on the other hand, those regarding the appreciation of the trailers by the students were measured as well. Two different trailers of the same movie were edited in order to control the narrative structure of the trailers (the independent variable).